PEMBERIAN MEDIA POSTER MELALUI INSTAGRAM SEBAGAI PSIKOEDUKASI TENTANG PENCEGAHAN TAWURAN REMAJA - Dian Novita Siswanti,; Muh. Daud,; Novita Maulidya Jalal,; Khezia Anom Sari P,; Nurmilasari Nurmilasari,; Sunarty Sunarty, (JURNAL PENGABDIAN MANDIRI, 2022)
Psychoeducation through poster media aims to provide information to teenagers regarding the prevention of brawls. The method used is to use an intervention in the form of psychoeducation including preparation, implementation of psychoeducation by disseminating posters about preventing brawls on Instagram, then an evaluation via google form at the end of the activity. The activity was carried out for 22 days starting from preparation to evaluation. However, the implementation of psychoeducation lasted for 1 week. The results of the service show that the dedication program for providing posters through Instagram (Ig) media as psychoeducation about preventing adolescent brawls as many as 9 posters has been successfully implemented with the results that it can add insight, is easy to understand and is interesting to read by 25 teenagers using Instagram who follow psychoeducation up to evaluation, read and liked by 97 teenage Instagram users, and posters received positive responses by teenagers who read brawl prevention posters on Instagram.